Methods of Sound Data Compression –omparison of Different Standards - Nowak, N.; Zabierowski, W. (ХНУРЭ, 2011)
The following article is about the methods of sound data compression. The technological progress has facilitated the process of recording audio on different media such as CD-Audio. The development of audio data compression has significantly made our lives easier. In recent years, much has been achieved in the field of audio and speech compression. Many standards have been established. They are characterized by more better sound quality at lower bitrate. It allows to record the same CD-Audio formats using "lossy" or lossless compression algorithms in order to reduce the amount of data surface area at almost noticeable difference in the quality of the recording. In order to compare methods of sound data compression I have used Adobe Audition 3.0 software and computer program of the sound compression system from manufacturers’ side. To illustrate the problem, I have used the graphs of the spectrum and musical composition spectrograms. The comparison has been done on the basis of uncompressed music track from the original CD-Audio.
Keywords: comparison; FLAC; mp3; Terms—sound data compression